2022
DOI: 10.3390/md20060386
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Potential of Immunomodulatory Natural Products

Abstract: Cancer is one of the leading causes of death globally. Anticancer drugs aim to block tumor growth by killing cancerous cells in order to prevent tumor progression and metastasis. Efficient anticancer drugs should also minimize general toxicity towards organs and healthy cells. Tumor growth can also be successfully restrained by targeting and modulating immune response. Cancer immunotherapy is assuming a growing relevance in the fight against cancer and has recently aroused much interest for its wider safety an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 192 publications
3
11
0
Order By: Relevance
“…In line with our ndings, previous studies demonstrated the potential of natural products like polyphenols to restructure the immunosuppressive microenvironment of tumors and hinder tumor growth [72,73]. These natural products have been shown to downregulate the percentages of immunosuppressive cells, such as MDSCs, Tregs, and M2-MACs, while promoting the proportions and function of anti-tumor effector T cells like CD8 + T cells, CD4 + T cells, and NK cells [72][73][74]. Given that MH comprises a variety of polyphenols, it is perhaps not unreasonable to suggest that these bioactive substances contribute to the elicitation of the observed anti-tumor immune responses following MH treatment.…”
Section: Discussionsupporting
confidence: 91%
“…In line with our ndings, previous studies demonstrated the potential of natural products like polyphenols to restructure the immunosuppressive microenvironment of tumors and hinder tumor growth [72,73]. These natural products have been shown to downregulate the percentages of immunosuppressive cells, such as MDSCs, Tregs, and M2-MACs, while promoting the proportions and function of anti-tumor effector T cells like CD8 + T cells, CD4 + T cells, and NK cells [72][73][74]. Given that MH comprises a variety of polyphenols, it is perhaps not unreasonable to suggest that these bioactive substances contribute to the elicitation of the observed anti-tumor immune responses following MH treatment.…”
Section: Discussionsupporting
confidence: 91%
“…In the literature, it is suggested that tumor growth and proliferation can also be restrained by targeting and modulating the immune response. Natural immunomodulators can stimulate humoral and cell-mediated immune responses against the tumor [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several natural compounds that are able to induce necroptosis, a programmed form of necrosis, are currently being evaluated in prostate cancer therapy (Beretta & Zaffaroni, 2022). Modulation of the immune system is being increasingly sought by pharmaceutical companies in cancer immunotherapy approaches, and several natural compounds have been investigated alone or in combination with conventional cancer therapy (Nuzzo et al, 2022). Considering that several medicinal agents are originated from natural resources and since the ancient period have been used as therapeutic agents (Muhammad et al, 2022), the identification of new compounds with cytotoxic activity against cancer cells and the capacity to induce inflammatory response warrants further investigation.…”
Section: Cytotoxicity Effects Of Compounds 1-5mentioning
confidence: 99%